2018
DOI: 10.1017/s0950268818000249
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and control measures of an OXA-48-producing Enterobacteriaceae hospital-wide oligoclonal outbreak

Abstract: The main objective of our study was to describe the epidemiological and microbiological features of an oligoclonal hospital-wide outbreak caused by OXA-48-producing Enterobacteriaceae (OXA-48-PE). OXA-48 is a carbapenemase belonging to Ambler class D beta-lactamases, identified frequently in the Mediterranean and Southern European countries, and associated with several Enterobacteriaceae species. An outbreak of OXA-48-PE with a complex epidemic pattern was detected in January 2011. Initial control measures inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…OXA-48-producing K. pneumoniae were first detected in our hospital in December 2010 and have spread through several hospital units since then (Paño-Pardo et al, 2013;Pérez-Blanco et al, 2018). Two major and several minor sporadic clones have been identified.…”
Section: Introductionmentioning
confidence: 90%
“…OXA-48-producing K. pneumoniae were first detected in our hospital in December 2010 and have spread through several hospital units since then (Paño-Pardo et al, 2013;Pérez-Blanco et al, 2018). Two major and several minor sporadic clones have been identified.…”
Section: Introductionmentioning
confidence: 90%
“…The bla OXA-48 gene is often found in Tn1999 composite transposons that harbor copies of IS1999 flanking both sides of this ␤-lactamase gene (240). Isolates that express OXA-48 may be susceptible to cephalosporins and have only modestly elevated carbapenem MIC values, with many imipenem MICs of Յ2 g/ml (241,242). High-level resistance to carbapenems is usually due to a secondary nonenzymatic resistance mechanism in these isolates (239).…”
Section: Carbapenemase-producing Bacteriamentioning
confidence: 99%
“…The most common STs identified in nationwide surveillances were ST101 in the United Kingdom (30) and ST395 in Poland (95). Regional nosocomial outbreaks of different K. pneumoniae STs have been reported from various countries, including the following: ST11, ST101, and ST405 in Spain (84), ST147 in Germany (131) and Slovenia (99), and ST11 in Croatia (98) and Spain (133). The analysis of the K. pneumoniae ST147 outbreak in Germany showed that bla OXA-48 was harbored on pOXA-48a-like IncL plasmids, while bla CTX-M-15 and other antimicrobial resistance genes were situated within IncR and IncC plasmids (131).…”
Section: Genetic Environments Surrounding Bla Oxa-48mentioning
confidence: 99%